Definite vacuum for strong-field quantum electrodynamics experiments - Qiqi Yu; Baifei Shen; Stefan Bock; Ulrich Schramm; Thomas E. Cowan; Roland Sauerbrey; Hans-Peter Schlenvoigt (High Power Laser Science and Engineering)
Ultra-intense lasers can generate the strongest electromagnetic fields in laboratory conditions, and are expected to perform tests of quantum electrodynamics (QED) in yet unexplored parameter ranges. Such experiments require knowledge of the field strengths and all possible interaction pathways. The latter can be simplified if a perfect, particle-free vacuum is present, thereby excluding competing interactions. We propose a method to evacuate all residual gas particles prior to QED interactions, based on tunnel ionization by a preceding auxiliary laser pulse and a static electric field. We present modelling and experimental results of testing this method on a